The imagined audience in social media: a systematic review - Sun, Jingle; Ahmad Ghazali, Akmar Hayati; Saiful Nujaimi Abdul, Rahman (Redfame Publishing Inc., 2024)
Determining the audience for social media posts is complex due to platform algorithms and mixed audiences. The "invisible audience" and the collapse of distinct social contexts challenge users’ capacity to manage their social circles effectively. This systematic review, adhering to PRISMA guidelines, identified 17 relevant articles through a structured search and screening. It outlines study backgrounds, sample characteristics, data collection methods, and highlights factors influencing audience categorization, aiding the understanding of imagined audience formation. The review discusses the impact of imagined audiences on user behavior and emotions, distinguishing these effects and enriching existing research. It aims to enhance users' audience awareness, improve privacy management, and support technology and literacy efforts related to social media privacy challenges.